2010
DOI: 10.1111/j.1439-0507.2010.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum and surface characteristics on Candida albicans biofilm formation

Abstract: Candida spp. biofilms can be established on a wide range of materials, including implanted medical devices, and can display a resistant phenotype to antifungal drugs. Several factors, including host and surface properties, may influence the establishment and the development of Candida albicans biofilms on biotic and abiotic surfaces. We therefore selected a collection of C. albicans clinical isolates to evaluate the effect of surface and serum on biofilm attachment and development. Disc coupons from the CDC bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 31 publications
1
35
0
2
Order By: Relevance
“…It has been shown that the degree of biofilm formation varies and correlates with five different switch phenotypes of C. albicans (12). Several factors, including host and surface properties, artificial saliva and different environmental conditions affect biofilm formation in C. albicans (25-27). In addition, biofilm formation also differed among different species of Candida (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the degree of biofilm formation varies and correlates with five different switch phenotypes of C. albicans (12). Several factors, including host and surface properties, artificial saliva and different environmental conditions affect biofilm formation in C. albicans (25-27). In addition, biofilm formation also differed among different species of Candida (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that an increase of the hydrophobicity and roughness of surface materials leads to elevated biofilm formation by Candida spp. (9,10). Adhesion molecules involved in surface adhesion have been well characterized in C. albicans.…”
mentioning
confidence: 99%
“…C. albicans is known to interact with these ubiquitous matricellular proteins through specific interactions, which may enhance tissue invasion and contribute to virulence (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Given the evidence for the likely involvement of these proteins in Candida pathogenicity, pioneering biofilm investigations have emphasized the importance of a host conditioning fluid for optimal biofilm formation and the need to account for the proteins in in vitro biofilm models (29,35,(55)(56)(57)(58). However, little is known about how assimilation of host proteins may affect biofilm structure and function, perhaps even fostering biofilm development.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous host factors have been shown to influence fungal biofilms (27)(28)(29)(30)(31)(32). In vitro studies have often included proteins and other factors to mimic the niche site infection (1).…”
Section: Discussionmentioning
confidence: 99%